Analisis Hukum dan Beban Pembuktian terhadap Ketidakcakapan Salah Satu Pihak dalam Perjanjian - Mokhamad Fajar Zihady Faturrahman; Nadhil Najwan Putra Cahya; Na’imah Putri Rahayu; Radithya Fathan Al Gibran; Ribka Sri Rejeki Simanjuntak (Mahalini: Journal of Business Law, 2024)
AbstractThe incompetence regulations listed in the laws and regulations have a lot of regulations, these various variants cause many consequences as well because it will make it easy for people to be able to take legal actions because they are considered competent. However, of course, this diversity also causes abuse of the applicable regulations because of the flexibility of choice in becoming competent and making it easier to abuse what is not yet their authority. This paper will use a combination of books, journals and academic articles that discuss the need to develop a positive attitude along the way. This research emphasizes the need for legislation as a basis for being able to conduct research. This research analyzes the burden of proof of an incapable person who has signed an agreement, the purpose of clarifying and providing an understanding of what kind of burden of proof must be issued and what can be done by an incapable person in proving it in an authentic deed.Â